Load Bearing and Deformation Characteristics of Granular Spoils under Unconfined Compressive Loading for Coal Mine Backfill - Guodong Li; Shugang Cao; Yong Li; Zhenyu Zhang (Advances in Materials Science and Engineering)
The load bearing capacity and deformation response of granular spoils under uniaxial compression are numerically and experimentally investigated, aiming to shed light on the performance of back filled waste spoils while controlling ground subsidence after coal extraction. In numerical study, the particles are assembled in PFC commercial code in light of the digitized real shape of spoils with image technique, which is proved to be consistent with the physical test. The results from numerical and laboratory experiments showed that the complete compressive process of spoils tended to have spatial and temporal characteristics. The load-strain curves of investigated specimens could be divided into three stages (stage I, rearranging stage; stage II, breaking stage; stage III, consolidating stage) and three zones (I, rearranging zone; II, interlocking zone; III, consolidated zone) from outside to inside. During stage I, the load increasing rate of smaller spoils is relatively low, but it increases faster than larger ones in stages II and III. In addition, spoils with Talbot’s gradation are greater than single gradations. The magnitude of the density in consolidated zone is maximum, indicating that it is the main part holding the overlying strata weight.